In Search of Appropriate Pedagogy that Could Enhance Students’ Interest and Academic Achievement in Qualitative Analysis: A Consideration of Predict-Observe-Explain-Explore (POEE) and Demonstrate-Observe-Explain (DOE) Strategies? - Rachael Folake Ameh; Endurance Nubagbi Sor; Victor Oluwatosin Ajayi (Journal of Advanced Research in Education, 2025)
This research investigated if secondary school students’ interest and achievement in the context of qualitative analysis could be enhanced using predict-observe-explain-explore (POEE) or demonstrate-observe-explain (DOE) instructional strategies. The study was conducted in Kogi Central Education zone of Kogi State, Nigeria. The study adopted quasi-experimental design. 1489 senior secondary three (SS3) students offering chemistry was the population of the study. The sample of the study was 206 students offering chemistry drawn from the population using purposive sampling technique. Qualitative Analysis Interest Questionnaire (QAIQ) and Qualitative Analysis Academic Achievement Test (QAAAT) were the instruments used for data collection. Cronbach’s Alpha was used to calculate the reliability coefficient of QAIQ which yielded 0.93 while the Kendell Coefficient of Concordance was used to calculate the inter-rater reliability of the QAAAT which yielded 0.86. Mean and standard deviation were used to answer the four research questions while analysis of co-variance (ANCOVA) was used to test the four null hypotheses that guided the study. The finding revealed that that the mean difference in the interest rating between the groups (POEE group and DOE group) was significant in favour of POEE group [F1, 205=4.604, P<0.05]. It was further revealed that the mean difference in the academic achievement scores between the groups was statistically significant in favour of POEE [F1, 205=89.004, P<0.05]. Thus, it was recommended that in-service chemistry teachers should be encourage to adopt POEE strategy in order to enhance students’ interest and academic achievement in the context qualitative analysis.